Colors in Glasses - de Ligny, Dominique; Möncke, Doris (Springer Handbook of Glass, 2019)
Glass is a fascinating material, not only because of its transparency and for its formability, but also because of the manifold facets of bright colors it can display. Just remember how the colored glasses of cathedral windows made us dream in our childhood, and how much we could quarrel in the schoolyard over a marble or a bead necklace. In this chapter, we will attempt to understand the physical origin of different colors and by what chemical processes, hues, and intensity of colors can be controlled in glasses. However, to do so, we must first understand what a color is, and only then will we be able to discuss how the different active color centers, when incorporated into a vitreous matrix, the glass, can create such a variety of responses toward light. We want to focus especially on the most frequent and, thus, typical causes of glass coloring, that is, the mechanisms of absorption. Examples from many transition metal ions will illustrate how their valence, local structure, or relation to other elements can impact the final glass color. The role of plasmon-resonance, involving metallic nanoparticles will also be described. However, other light effects due to reflection and scattering in the bulk or at the surface of a glass can also induce colors. For example, the iridescence of corroded glasses, which originates from multireflection on an alteration layer, can be exploited as an artistic effect. Light scattering by crystals or phase separation also plays an important role, since it gives us the option to modify the aspect from transparent to opalescent or to opaque. Finally, we will present some color-related functionalization of glasses such as photochromism and electrochromism. Many more details on glass and colors can be found in the literature, e. g., [9.1, 9.2, 9.3].
CRIS-Team Scopus Importer:2019-12-13